Strategi Jumput sebagai Upaya Peningkatan Keterampilan Membaca Puisi pada Siswa Kelas V MIN Se-Kota Palembang - Hetilaniar Hetilaniar (Jurnal Dosen Universitas PGRI Palembang)
AbstractThis research is intended to improve students' ability in reading poetry. During this learning model that is implemented in learning activities in MIN Palembang city level still using conventional learning model so that the results obtained less than the maximum. One of the learning method to improve the learning result of writing the poem by using jumput strategy. To measure the level of success in the mastery of poetry reading ability, students are given the task of reading poetry at the end of the learning action activities as an evaluation tool. Based on the results of research that has been done in the pre-cycle stage, cycle I and cycle II students of class V Min in Palembang City in the study of poetry, executed that JUMPUT strategy used to improve the skill of reading poetry students. This is based on the increase that occurs at each stage starting from the pre-cycle stage of only 1.7% to 30.5% in cycle I and a very significant increase occurred in the second cycle of 89.8%.Keywords: Reading Poetry, JUMPUT Strategy